Image Politics in the Contest for the Regional Head Election of Gianyar Regency in the Reform Era - I Made Artayasa; Ni Wayan Anggreni; I Kadek Dede Junaedy (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Direct local elections, as a reform response, have driven regional head candidates in Gianyar Regency, Bali, to adopt various strategies to win the contest. The candidates use image politics by crafting cultural activities as part of their political art to build a positive image in all available spaces. The primary goal of these image-building efforts is to shape public opinion and gather support. This approach also serves as a means of communication, allowing candidates to address the aspirations of grassroots communities directly. This study employed qualitative research methods, starting with observation, document collection, online data searches, and in-depth interviews with informants. The research identified various forms of image politics used by regional head candidates in Gianyar during the reform era elections. These included community engagement activities like simakrama (gatherings with traditional communities), collective prayers at temples and subak (irrigation associations), free medical services, fishing events, and blood donation drives. These efforts aimed to build a positive public image and connect with voters directly.